2014
DOI: 10.3109/10715762.2014.945442
|View full text |Cite
|
Sign up to set email alerts
|

Bilobalide attenuates hypoxia induced oxidative stress, inflammation, and mitochondrial dysfunctions in 3T3-L1 adipocytes via its antioxidant potential

Abstract: Excessive expansion of white adipose tissue leads to hypoxia which is considered as a key factor responsible for adipose tissue dysfunction in obesity. Hypoxia induces inflammation, insulin resistance, and other obesity related complications. So the hypoxia-signalling pathway is expected to provide a new target for the treatment of obesity-associated complications. Inhibition or downregulation of the HIF-1 pathway could be an effective target for the treatment of obesity related hypoxia. In the present study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Bilobalide has four five-membered rings (three lactones and a carbocycle) and a tert-butyl group. Many terpene lactones are reported to have anti-inflammatory [6,7], endothelial protective [8,9], cardioprotective [10], antiplatelet [11], and antioxidant properties in cell-based and animal-based studies [12,13]. Ginkgolides A, B, and C are also platelet-activating factor (PAF) receptor antagonists [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Bilobalide has four five-membered rings (three lactones and a carbocycle) and a tert-butyl group. Many terpene lactones are reported to have anti-inflammatory [6,7], endothelial protective [8,9], cardioprotective [10], antiplatelet [11], and antioxidant properties in cell-based and animal-based studies [12,13]. Ginkgolides A, B, and C are also platelet-activating factor (PAF) receptor antagonists [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, ONOO − and H 2 O 2 may partly convert into OH • . Bilobalide has antioxidant potential through promoting antioxidase expression in a variety of cell types . We failed to get a special reagent for indication of intracellular ONOO − but HPF, a fluorescence probe reactive to OH • and ONOO − .…”
Section: Discussionmentioning
confidence: 98%
“…32 Multiple stimuli such as growth factors and fluid shear stress activate eNOS by Ser-1177 phosphorylation 33 Bilobalide has antioxidant potential through promoting antioxidase expression in a variety of cell types. 18,19,24,25 We failed to get a special reagent for indication of intracellular ONOO À but HPF, a fluorescence probe reactive to OH • and ONOO À . Our present data showed that bilobalide pre-treatment limited the increase of OH • / ONOO À , O 2 À • and H 2 O 2 in proliferating OECs, implying bilobalide F I G U R E 8 Effect of bilobalide on hydroxyl radical/peroxynitrite, superoxide anion and hydrogen peroxide in proliferating lateoutgrowth endothelial cells (OECs).…”
Section: Discussionmentioning
confidence: 99%
“…These changes lead to cells deterioration, resulting in insulin resistance or in a greater lipid accumulation in adipocytes, due to the increased nicotinamide adenine dinucleotide phosphate-reduced (NADPH) supply, predisposing to obesity by changes in energy metabolism [4,20] . Hypoxia, from adiposity excess significantly alter the adipocytes vital parameters, such as: the increase in ROS (432.53%), lipids and proteins oxidation (376.6% and 566.6%, respectively), the antioxidant enzymes and inflammatory mediators release reduction [21] . Thus, the adiposity excess and oxidative stress observed in obesity trigger an inflammatory cascade by phosphorylation of signal transduction and activation of transcription (STAT) pathways -Jun N-terminal kinase proteins (JNK); Nuclear Factor kappa Beta (NF-KB) [22] .…”
Section: Obesity Energy Metabolism and Inflammationmentioning
confidence: 99%